Dampak Tata Kelola Perusahaan yang Efektif, Profitabilitas, dan Leverage terhadap Pengungkapan Manajemen Risiko Perusahaan - Ardinitya Hangesti Utami; Martinus Budiantara (Income Journal: Accounting, Management and Economic Research, 2024)
The quick advancement of the business sector has resulted in an increasing intensity of business competition. Therefore, to maintain the trust of stakeholders, each company is expected to disclose information about its company's performance more transparently and always be careful in making policies to minimize various risks that may arise. In the business world, risk is something that is quite difficult to avoid so that adequate disclosure of risk is needed through risk management disclosure. The objective of this research is to examine the impact of good corporate governance, profitability, and leverage on the disclosure of risk management in manufacturing firms within the basic and chemical industry sectors that are enlisted on the Indonesia Stock Exchange during the period of 2019-2021. The number of samples used was 51 samples using the purposive sampling method. The variables that will be considered as independent in this research consist managerial ownership, public ownership, profitability, and leverage. On the other hand, the variable that will be considered as dependent is risk management disclosure. The analysis technique used were multiple linear regression analysis and the t test using SPSS 26 software. The research results showed that the variables of public ownership and leverage affect risk management disclosure while the variables of managerial ownership and profitability have no effect on risk management disclosure. The results of this research can provide additional information for companies regarding risk management disclosure and can help companies make decisions and improve existing systems in the company.